Predicted alpha-helical regions of the prion protein when synthesized as peptides form amyloid. - Gasset, M (1992)
By comparing the amino acid sequences of 11 mammalian and 1 avian prion proteins (PrP), structural analyses predicted four alpha-helical regions. Peptides corresponding to these regions of Syrian hamster PrP were synthesized, and, contrary to predictions, three of the four spontaneously formed amyloids as shown by electron microscopy and Congo red staining. By IR spectroscopy, these amyloid peptides exhibited secondary structures composed largely of beta-sheets. The first of the predicted helices is the 14-amino acid peptide corresponding to residues 109-122; this peptide and the overlapping 15-residue sequence 113-127 both form amyloid. The most highly amyloidogenic peptide is AGAAAAGA, which corresponds to Syrian hamster PrP residues 113-120 and is conserved across all species for which the PrP sequence has been determined. Two other predicted alpha-helices corresponding to residues 178-191 and 202-218 form amyloids and exhibit considerable beta-sheet structure when synthesized as peptides. These findings suggest the possibility that the conversion of the cellular isoform of PrP to the scrapie isoform of PrP involves the transition of one or more putative PrP alpha-helices into beta-sheets and that prion diseases are disorders of protein conformation.